Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.3389/fpsyg.2019.01633
|View full text |Cite
|
Sign up to set email alerts
|

Learning From the Past to Advance the Future: The Adaptation and Resilience of NASA’s Spaceflight Multiteam Systems Across Four Eras of Spaceflight

Abstract: Many important “grand” challenges—such as sending a team of humans on a voyage to Mars—present superordinate goals that require coordinated efforts across “multiteam systems” comprised of multiple uniquely specialized and interdependent component teams. Given their flexibility and resource capacity, multiteam system structures have great potential to perform adaptively in dynamic contexts. However, these systems may fail to achieve their superordinate goals if constituent members or team… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…This first overarching theme echoes other research on collective collaboration. Past MTS research has indicated that component teams, and especially failing teams and teams under stress, turn their attention and behaviors inwards ( Kanfer and Kerry, 2012 ; Beck and Plowman, 2014 ; Stoate, 2015 ; Wijnmaalen, 2015 ; Rico et al, 2016 , 2018 ; Bick et al, 2017 ; Schecter, 2017 ; Schipper, 2017 ; Schipper and Gerrits, 2017 ; Wijnmaalen et al, 2018 , 2019 ; Pendergraft et al, 2019 ; Ziegert et al, 2020 ; Torres et al, 2021 ). Both cognitive and motivational mechanisms explicate this trend in failing MTSs.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…This first overarching theme echoes other research on collective collaboration. Past MTS research has indicated that component teams, and especially failing teams and teams under stress, turn their attention and behaviors inwards ( Kanfer and Kerry, 2012 ; Beck and Plowman, 2014 ; Stoate, 2015 ; Wijnmaalen, 2015 ; Rico et al, 2016 , 2018 ; Bick et al, 2017 ; Schecter, 2017 ; Schipper, 2017 ; Schipper and Gerrits, 2017 ; Wijnmaalen et al, 2018 , 2019 ; Pendergraft et al, 2019 ; Ziegert et al, 2020 ; Torres et al, 2021 ). Both cognitive and motivational mechanisms explicate this trend in failing MTSs.…”
Section: Resultsmentioning
confidence: 99%
“…Our methodological approach builds upon case study analysis methods used in recent MTS studies (e.g., Pendergraft et al, 2019 ; Torres et al, 2021 ), leveraging historiometric analysis (HMA; Simonton, 2003 ; Crayne and Hunter, 2018 ) to conduct a structured examination sof MTS performance situations and contexts. In a recent review, Burke et al (2021) describe historiometry as “special case of archival analysis,” unique for its use of quantification to support qualitative data analysis of historically significant events.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Context matters, and certain industries have embraced the importance of team dynamics as the links between team functioning and valued organizational outcomes in that industry are particularly salient. Articles in this special address spaceflight (Bell et al, 2019 ; Pendergraft et al, 2019 ) military (Demir et al, 2019 ; Johnston et al, 2019 ), healthcare (Stevens et al, 2019 ), and isolated and confined environments (Landon et al, 2019 ). While this list of industries is by no means exhaustive of those pursuing team-based work strategies or engaged in research efforts to understand and improve team dynamics, it is representative of the key contributors.…”
Section: High Risk/high Stake Industries Are Leading the Way For Teammentioning
confidence: 99%